Early-age elastic properties of cement-based materials as a function of decreasing moisture content. (November 2016) - Di Bella, Carmelo; Griffa, Michele; Ulrich, T.J.; Lura, Pietro
Abstract: The moisture content is of particular relevance in cement-based materials, as it has a strong impact on their fundamental material properties. For example, it directly affects their strength and elastic properties, which in turn are closely related to volumetric deformations and cracking susceptibility. This paper investigates the influence of the decreasing moisture content on the elastic properties at early-ages, when the material properties are still developing simultaneously to the drying process. Mortar mixtures containing either Portland cement or cement blended with slag were specifically designed to halt the hydration at predefined stages without altering the microstructure or promoting further hydration during drying (equivalent systems). The elastic modulus of the equivalent mortars as a function of the moisture content is measured through resonant ultrasound spectroscopy. At early age the elastic modulus remained constant during drying, while at later ages a steady reduction was observed as a function of the decreasing relative humidity.